2020
DOI: 10.1002/csr.2099
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Corporate Social Responsibility on Corporate Image: Evidence of budget airlines in Europe

Abstract: There is growing scientific debate on the impact of Corporate Social Responsibility (CSR) or Corporate Hypocrisy (CH) on Corporate Reputation (CR). The aim of the study is to analyse the influence of CSR on CR based on literature review and results of conducted empirical studies and to test this relationship in growing budget airlines sector. Environmental responsibility of airlines was highlighted in this study. The empirical study conducted in Lithuania employed quantitative survey. And 400 adults were surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…With corporate social responsibility (CSR) now a major part of many business practices, the airline industry is under growing pressure to provide a clean, safe, and reliable transportation service to their employees and passengers [1,2]. However, the recent COVID-19 pandemic posed new CSR challenges for an industry struggling to stay viable.…”
Section: Introductionmentioning
confidence: 99%
“…With corporate social responsibility (CSR) now a major part of many business practices, the airline industry is under growing pressure to provide a clean, safe, and reliable transportation service to their employees and passengers [1,2]. However, the recent COVID-19 pandemic posed new CSR challenges for an industry struggling to stay viable.…”
Section: Introductionmentioning
confidence: 99%
“…Wagner et al (2009) introduced corporate hypocrisy in the marketing field and conceptualized the inconsistency between a company's CSR actions and its pitch as corporate hypocrisy. Several recent studies have indicated that corporate hypocrisy is the CSR belief that a firm claims to be something that it is not (Shim and Kim, 2017;Streimikiene et al, 2020).…”
Section: Literature Review and Theoretical Framework 21 Corporate Hyp...mentioning
confidence: 99%
“…Such understanding of responsible business means that CSR is noticed by stakeholders and influences the perception of the company. Companies strive to implement their strategic plans and maximize profits, taking into account the economic, social, and environmental issues that arise in their operations (Streimikiene et al, 2020 ). Based on the opinion of the European Commission, Stoian and Gilman ( 2017 ) define CSR as the responsibility of enterprises for their impact on society.…”
Section: The Area Of Corporate Social Responsibility Activitiesmentioning
confidence: 99%